Cell‐surface binding domains from Clostridium cellulovorans can be used for surface display of cellulosomal scaffoldins in Lactococcus lactis. Issue 8 (7th June 2021) - Tarraran, Loredana; Gandini, Chiara; Luganini, Anna; Mazzoli, Roberto
Abstract: Engineering microbial strains combining efficient lignocellulose metabolization and high‐value chemical production is a cutting‐edge strategy towards cost‐sustainable 2 nd generation biorefining. Here, protein components of the Clostridium cellulovorans cellulosome were introduced in Lactococcus lactis IL1403, one of the most efficient lactic acid producers but unable to directly ferment cellulose. Cellulosomes are protein complexes with high cellulose depolymerization activity whose synergistic action is supported by scaffolding protein(s) (i.e., scaffoldins). Scaffoldins are involved in bringing enzymes close to each other and often anchor the cellulosome to the cell surface. In this study, three synthetic scaffoldins were engineered by using domains derived from the main scaffoldin CbpA and the Endoglucanase E (EngE) of the C. cellulovorans cellulosome. Special focus was on CbpA X2 and EngE S‐layer homology (SLH) domains possibly involved in cell‐surface anchoring. The recombinant scaffoldins were successfully introduced in and secreted by L. lactis . Among them, only that carrying the three EngE SLH modules was able to bind to the L. lactis surface although these domains lack the conserved TRAE motif thought to mediate binding with secondary cell wall polysaccharides. The synthetic scaffoldins engineered in this study could serve for assembly of secreted or surface‐displayed designer cellulosomes in L. lactis . Abstract : Engineering microbial strains combining efficient lignocellulose metabolization and high‐value chemical production is a cutting‐edge strategy towards cost‐sustainable 2 nd generation biorefining. Here, Lactococcus lactis (efficient lactic acid producer) was engineered with synthetic scaffoldins for assembly of secreted and cell‐surface displayed designer cellulosomes.